THE REASONS OF DIFFERENTIAL WALL STICKING IN DRILLING OIL AND GAS WELLS - Nalivaiko, О.; Nalivaiko, L.; Reznichenko, A.; Chyhyriov, V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
Of the article raised the question of occurrence the causes of differential wall sticking.An attempt to analyze the mechanism of differential wall sticking in drilling oil and gas wellswas made. Operations in liquidation of wall sticking and casing pipe that occur in drilling arethe most difficult and time-consuming. One of the ways to improve the requirements ofcasingstring cementing is the use of different chemical additives in cement that change the structureof well cement. One of them is hydrophobic additive «Silpan-Р», which effectiveness isdescribed in the article. Own view on the issue of process occurrence of differential wallsticking that is different from the existing ones was offered.Keywords: drill string, differential sticking, osmosis, hydrophobic additive «Silpan-Р»,well, pressure.